Locking out emotions in locking up older prisoners?: Emotional labour of Belgian prison officers and prison nurses - Humblet, Diete (International journal of law, crime and justice, 2020)
This contribution looks at the emotional labour of prison professionals in the wake of an increasing number of older adults populating this institution. The rationale behind this selective focus is twofold. Firstly, the topic of ageing behind bars has only received scant attention, even though this phenomenon is also increasingly penetrating prison walls. Secondly, little attention has been paid to the performance of emotional labour by practitioners in prison systems working with the specific population of ageing prisoners. Against this background, this contribution reflects on the ambivalent emotional nature of the work of not only the ‘professionals of custody’ but also of the ‘professionals of care’ in a prison setting. This topic will be examined by drawing on cross-disciplinary insights stemming from a wider range of literature and is underpinned by new data originating from an empirical ethnographic study into the meaning of imprisonment in later life in Belgium.